Draw the Circle Wide(r): Analisis Naratif terhadap Kejadian 1 dan 2 dalam Perspektif Antropologi Gender sebagai Upaya Tafsir Inklusif Gender - Dia Gloria Ekklesia (Theologia in Loco, 2022)
This paper interprets Genesis 1 and 2 (creation narrative) using a gender anthropological perspective as an attempt to show gender inclusiveness in Genesis 1 and 2 that embraces gender minorities. Starting from the awareness of the marginalization of gender minorities both inside and outside the church using the biblical text, this article emphasizes that the marginalization of gender minorities is not the main message of Genesis 1 and 2. This paper begins by discussing the context of marginalization of gender minorities using biblical texts to legitimize violence against minority gender identities or orientations. Then this article uses an inclusive gender interpretation of Genesis 1 and 2 to demonstrate an anthropological-based inclusive interpretation of gender injustice and gender justice.